Krepšininkiu kuno kompozicijos ir mitybos vertinimas - Baranauskas, M.; Kupciunaite, I.; Lieponiene, J.; Stukas, R. (Sporto Mokslas-Sport Science, 2024)
Optimal nutrition goals are undoubtedly related to the general health and fitness of athletes. Scientific literature lacks data on the nutritional status in basketball players representing both the Lithuanian Olympic Shift and Deaflympics` Team. The existing gap in this scientific field does not allow the optimization of athletes` diet at a level that could fully ensure bodily adaptation to intensive and/or long-term physical loads in basketball players. The cross-sectional study aimed to assess and evaluate the body composition and nutritional profiles among Lithuanian female basketball players from Olympic shift and Deaflympics` Team. During the preparatory period, junior female basketball players (n = 13; age: 18.1 ± 0.5 years) as well as these ones preparing for the Deaflympics (n = 12; age: 26.9 ± 4.9 years) were recruited to the study. Body composition of female athletes was analysed using the bioelectrical impedance approach (BIA). A dietary assessment of female athletes was conducted using a standardized 7-day dietary recall method. The study results revealed that the body composition of Lithuanian female basketball players was satisfactory. More specifically, depending on the relatively higher body fat percentage, the muscle-to-fat ratio was below the one average recommended for deaf basketball players. If comparing international recommendations with the amounts of carbohydrates consumed by basketball players (5.1 g/kg to 5.4 g/kg) we studied, it is possible to predict the chronic deficit of carbohydrates intake among Lithuanian female basketball players. Furthermore, in diets of deaf basketball players, the fat percentage (37.3%) exceeded the recommendations. Finally, fat-soluble vitamin D was only deficient in the diets were eaten by the Olympic shift basketball players.